Biodegradation of films of low density polyethylene (LDPE), poly(hydroxibutyrate-co-valerate) (PHBV), and LDPE/PHBV (70/30) blend with Paecilomyces variotii - Passos, Thayse Marques [UNESP]; Marconato, Jose Carlos [UNESP]; Martins Franchetti, Sandra Mara [UNESP] (Assoc Brasil Polimeros, 2015)
The increased consumption of plastics in the world has been a subject of great concern and special attention by the scientific community. The aim is to promote development of materials that are biodegradable in a shorter time upon disposal in the environment. The most used synthetic plastics are difficult to biodegrade because they are made of long hydrocarbon chains, such as polyethylene (PE), polypropylene (PP), poly(vinyl chloride) (PVC), which are hydrophobic and resistant to the action of microbial enzymes. The use of alternative materials (natural polyesters) can minimize the harm to dumps and landfills upon their disposal, because they are susceptible to the action of microorganisms. In this study we evaluated the biodegradation/biodeterioration of PHBV (poly(3-hydroxybutyrate-co-hydroxyvalerate) films, LDPE (low density polyethylene) and the blend of LDPE/PHBV (70/30) by the fungus Paecilomyces variotii, using different methods: optical microscopy (OM), scanning electronic microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR).
Keywords: Biodegradation; Paecilomyces variotii; FTIR; SEM